2016
DOI: 10.1038/srep36590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NDRG1 family proteins on photoreceptor outer segment morphology in zebrafish

Abstract: Rods and cones are functionally and morphologically distinct. We previously identified N-myc downstream-regulated gene 1b (ndrg1b) in carp as a cone-specific gene. Here, we show that NDRG1b and its paralog, NDRG1a-1, contribute to photoreceptor outer segment (OS) formation in zebrafish. In adult zebrafish photoreceptors, NDRG1a-1 was localized in the entire cone plasma membranes, and also in rod plasma membranes except its OS. NDRG1b was expressed specifically in cones in the entire plasma membranes. In a deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…For example, NDRG1 has been reported to have an association with stress response, cell proliferation, and differentiation (49)(50)(51); NDRG1 has been identified as a metastasis suppressor in a variety of cancers (52); and NDRG1 knockout mice experience autonomous dysfunction of Schwann cells and exhibit progressive demyelination in peripheral nerves (53). In zebrafish, there are two orthologs of the mammalian NDRG1, which are termed NDRG1a (consisting of two variants, NDRG1a-1 and NDRG1a-2) and NDRG1b (54). The two splice variants of NDRG1a are different only at their N-terminal amino acid sequences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, NDRG1 has been reported to have an association with stress response, cell proliferation, and differentiation (49)(50)(51); NDRG1 has been identified as a metastasis suppressor in a variety of cancers (52); and NDRG1 knockout mice experience autonomous dysfunction of Schwann cells and exhibit progressive demyelination in peripheral nerves (53). In zebrafish, there are two orthologs of the mammalian NDRG1, which are termed NDRG1a (consisting of two variants, NDRG1a-1 and NDRG1a-2) and NDRG1b (54). The two splice variants of NDRG1a are different only at their N-terminal amino acid sequences.…”
mentioning
confidence: 99%
“…The two splice variants of NDRG1a are different only at their N-terminal amino acid sequences. Recently, a study has reported that NDRG1 family proteins are involved in forming a normal outer segment shape in zebrafish photoreceptors (54). However, how NDRG1 is involved in antiviral immune response, if it is at all, is still unclear.…”
mentioning
confidence: 99%
“…To explore whether the NDRG family member(s) contribute to photoreceptor-specific cell loss, we originally hypothesized that NDRG1 was the putative candidate, considering that NDRG1 is the only NDRG subtype currently found expression in the retina, and that NDRG1 is involved in forming a normal morphological shape in zebrafish photoreceptors 19 . Accordingly, we indeed detected major distribution of NDRG1 in the inner segment/outer segment (IS/OS) of photoreceptor cells 29 , while NDRG1 was also present in the inner plexiform layer (IPL)/ganglion cell layer (GCL), as well as the outer plexiform layer (OPL) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating data also suggest organ/tissue-specific biological function of NDRGs in development and postnatal homeostasis, among which NDRG1, 2, and 4 are widely distributed in the nervous system and are involved in neural degenerative diseases 15 17 . Particularly, for the specialized neurons in the vertebrate retina, which include rod and cone photoreceptors, interneurons, and RGCs 18 , only NDRG1 has been documented expression with contributions to morphology in zebrafish photoreceptors, while NDRG2 was detected in murine astrocytes except the proliferative retinal Müller glia 19 , 20 . At the present time, it is unclear as to whether existence and altered level(s) of certain NDRG subtype(s) correlate with functional outcomes in retinal damaging conditions, and whether the effects are cell-type specific.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of an eys tv predominantly expressed in the adult zebrafish eye and its novel splice variants by CAGE, cloning, and RNA-seq Orthologs of human EYS gene are absent in mice and rats but are conserved across many other species, including the freshwater teleost, zebrafish. Because zebrafish husbandry is easy, they are widely used for genetic studies (16). Therefore, we chose zebrafish as a model organism to obtain insights into the functions of EYS gene in vertebrate photoreceptors (10)(11)(12).…”
Section: Analysis Of Expression Of the 59 And 39 Portions Of Eys Tranmentioning
confidence: 99%